ANALISIS KEKUATAN GATE VALVE 2 9/16 3.000 PSI AKIBAT TEKANAN FLUIDA MENGGUNAKAN FINITE ELEMENT ANALYSIS SOLIDWORKS 2018 - Bisma Herlambang (President University, 2020)
Valve (valve) as one of the industrial products, is needed by companies engaged in controlling fluid flow for efficiency. This need is widely used by power companies and the oil and gas industry. The purpose of using valves is to limit and control liquids under high pressure conditions. One valve that is often used is the gate valve, which is a valve with a type of motion fully open and fully close. The demand for this gate valve requires a product with certain specifications to have a design with a good level of strength. In other words, a good valve product (valve), must have a good strength, safe and in accordance with the needs to be tested. This study aims to analyze the gate valve 2 9/16 WP 3,000 psi to ensure the valve produced is according to specifications, strong and resistant to fluid pressure. The method used is Finite Element Analysis (FEA) with the 2018 Solidworks software. The analysis is performed on the gate valve with a full open, full closed state and with gradual loading starting at 1,000 psi, 2,000 psi and 3,000 psi resulting from Computational Fluid Dynamics (CFD). The analysis was carried out at 300C, Based on the results of the analysis with FEA, it was stated that the gate valve 2 9/16 WP 3,000 psi was strong and safe to use. The safety factor value is significantly higher than the minimum permissible safety factor value.